STATS OF FISHERIES AND DISEASE CONTROL IN THE REPUBLIC OF NORTH MACEDONIA IN THE ERLY 21th CENTERY - Trajcovski, Aleksandar; Hristovski, Misho (Economics of Agriculture, 2022)
This review aims to show the current state of fisheries in the Republic of Northern Macedonia as well as the strategy for the prevention and control of World Organization for Animal Health (OIE) notifiable diseases in aquaculture in order to comply with European legislation. At the moment, Macedonia produces about 1,700 tons, which dominates the production of trout with 63% and carp with about 29% of the total production. This sector has had a constant. Positive growth in recent years, attracting new investors, especially in cold-water aquaculture. Although the consummation of 5 kg per capita of fish is modest, domestic production does not satisfy their needs, so the market is supplemented with fish imports. One of the conditions for this sector to continue to grow at such a pace is to limit losses in aquaculture production. The most serious limitation that serious producers deal with is the appearance of infectious diseases.